Derivatives from Aceh Qanun Number 04 of 2014 concerning Ikhtilath in Improving the Performance of Wilayatul Hisbah (WH) Lhokseumawe City - Yani, Ahmad; Muryali, Muryali; Arinanda, Arinanda (International Journal of Public Administration Studies, 2021)
Ikhtilath is an act of intimacy between a man and a woman who is not an open criminal. This has been regulated in Aceh Qanun Number 6 of 2014. In realizing Social Ecology based on Islamic Sharia values in Bandar Lhokseuamwe there are still problems where implementation is far from what is expected, as evidenced by the Ikhtilath incident in Lhokseumawe City, this shows a low level of compliance with communities and implementers who fail to realize social ecology. The problem studied is the use of Qanun Jinayat Number 6 of 2014 in Case 1 Point 25 regarding Ikhtilath in the Kingdom of Bandar Lhokseumawe. In theory, he assessed the Islamic Sharia Officer, Wilayatul Hisbah in improving organizational performance in the kingdom of Lhokseumawe. Methods of qualitative investigation and descriptive analysis approach. Techniques for collecting data by observing, interviewing and documenting.